Humanae vitae, 50 years later : embracing God's vision for marriage, love, and life : a compendium - Notare, Theresa, 1957- (The Catholic University of America Press, 2019)
"Experts representing a variety of disciplines including history, culture, theology, medicine, law, and psychology reflect upon the Catholic Church's teachings on marriage and licit methods for the regulation of births, on the occasion of the 50th anniversary of the papal document Humanae vitae. Includes selected bibliography"--